Genome-based Proteomic Analysis of Lignosus rhinocerotis (Cooke) Ryvarden Sclerotium - Yap, H.Y.Y.; Fung, S.Y.; Ng, S.T.; Tan, C.S.; Tan, N.H. (Ivyspring International Publisher, 2015)
Lignosus rhinocerotis (Cooke) Ryvarden (Polyporales, Basidiomycota), also known as the tiger milk mushroom, has received much interest in recent years owing to its wide-range ethnobotanical uses and the recent success in its domestication. The sclerotium is the part with medicinal value. Using two-dimensional gel electrophoresis coupled with mass spectrometry analysis, a total of 16 non-redundant, major proteins were identified with high confidence level in L. rhinocerotis sclerotium based on its genome as custom mapping database. Some of these proteins, such as the putative lectins, immunomodulatory proteins, superoxide dismutase, and aegerolysin may have pharmaceutical potential; while others are involved in nutrient mobilization and the protective antioxidant mechanism in the sclerotium. The findings from this study provide a molecular basis for future research on potential pharmacologically active proteins of L. rhinocerotis.